Towards Actionable Learning Outcomes - Banerjee, Shilpi; Chomal, Aanchal (JOURNAL OF INDIAN EDUCATION, 2020)
Annual Status of Education Report (ASER), and National Achievement Survey (NAS) routinely reports the crisis of Learning Outcomes in Indian school education.The identified primary reason for this crisis is stakeholders unclarity about the kind of desired learning for each subject and criteria of assessment. Learning Outcomes for elementary stage developed by National Council for Educational Research and Training (NCERT) states important knowledge, skills and dispositions students need to attain at the end of an academic year. This paper attempts to develop a deep understanding about how Learning Outcomes are derived from aims of school education and their characteristics. Furthermore, the paper proposes an approach of designing effective lesson plan by following suitable pedagogy and assessment strategies in classroom. The paper concludes with a set of recommendations to institutionalise Learning Outcomes at the systemic level for stakeholders including teachers, schools, government and the private sector to enable them to work towards building integrated and holistic solutions.